The Determinants of Intellectual Capital Disclosure on Firm Value: The Evidence on the Financial Companies in Indonesia - Nasution, Umar Hamdan; Iskandar, Eddy; Rangkuti, Sahnan; Idris, Idris (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: Firm value is the price of the firm that can be sold with a price agreement that will be paid by the buyer. A high stock price will increase the value of the company and increase the prosperity of the investors. Therefore, to attract the attention of buyers of company shares, companies must provide the best and most detailed financial information possible. As for information that can be disclosed in financial reports, namely intellectual capital. The presence of PSAK No. 19 concerning intangible assets marked the beginning of the phenomenon of intellectual capital in Indonesia. It turns out that although Intellectual Capital Disclosure has started to grow in Indonesia, the growth is still very small. Companies in Indonesia should be required to disclose their intellectual property, particularly in the financial industry. This is because the financial services sector which is highly dependent on information uses more intellectual capital in its operations than the industrial sector which relies more on tangible assets. As it is known, the disclosure of intellectual capital can provide an attraction for investors to increase the value of the company. This study aims to find out how factors such as firm age, leverage, profitability, and independent commissioners affect firm value through the disclosure of intellectual capital.Methodology: This study uses a sample of financial sector companies listed on the Indonesia Stock Exchange in 2020-2021 with a total population of 105 companies and a total sample of 83 companies. This research uses panel data.Finding: According to the findings of this study, business size, profitability, age, independent commissioners, and disclosure of intellectual capital have a beneficial impact on firm value of about 43%. However, leverage does not affect firm value. Furthermore, the mediation test results show that disclosure of intellectual capital is not able to mediate the relationship between the effect of firm size, leverage, profitability, and firm age on firm value. Only the influence of independent commissioners mediates firm value.Conclusion: For future researchers, it is expected to increase the research period and add other factors that influence the disclosure of intellectual capital.